Thorough QT/QTc Evaluation of the Cardiac Safety of Enarodustat (JTZ‐951), an Oral Erythropoiesis‐Stimulating Agent, in Healthy Adults. Issue 8 (23rd June 2021) - Pai, Sudhakar M.; Yamada, Hiroyuki; Kleiman, Robert B.; Zhuo, Rui; Huang, Qingtao (Mike); Koretomo, Ryosuke
Abstract: This study evaluated the effect of enarodustat on cardiac repolarization in healthy subjects. Enarodustat (20 and 150 mg [supratherapeutic dose]), placebo, and moxifloxacin (positive control, 400 mg) were administered orally to males and females (N = 54) in a crossover fashion. Continuous 12‐lead Holter electrocardiogram (ECG) data were obtained before and after dosing, and blood samples were obtained for pharmacokinetic assessments of enarodustat, its circulating metabolite (R)‐M2, and moxifloxacin. Central tendency analysis was performed for relevant ECG parameters, the relationship between individual‐corrected interval from beginning of the QRS complex to end of the T wave in the frontal plane (QTcI, the primary end point) and plasma concentrations of enarodustat and (R)‐M2 were assessed, and ECG waveforms were evaluated for morphological changes. The supratherapeutic dose resulted in 7‐ and 9‐fold higher geometric mean maximum concentrations for enarodustat and (R)‐M2, respectively, than the 20 mg dose. Based on time point analysis, the upper bound of the 2‐sided 90% confidence interval (CI) for QTcI did not exceed 10 milliseconds at any of the time points for either dose. Based on QTcI‐concentration analysis, the slopes for enarodustat and (R)‐M2 were not statistically different than 0, and the upper bounds of the 2‐sided 90% CI for QTcI at the geometric mean maximum concentrations for the supratherapeutic dose were 1.97 and 1.68 milliseconds for enarodustat and (R)‐M2, respectively. The lower bound of the 2‐sided 90% CI for moxifloxacin was ≥5 milliseconds, demonstrating assay sensitivity. The study demonstrated no clinically relevant effect of enarodustat and (R)‐M2 on cardiac repolarization. There was no evidence of any clinically significant effect on the PR interval and QRS duration, and ECG waveforms showed no new clinically relevant morphological changes.